2008
DOI: 10.1007/s10653-008-9217-2
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-biomonitoring of intra-urban spatial variations of particulate matter using tree leaves

Abstract: Preliminary mineral magnetic results from a pilot project investigating the suitability of roadside tree leaves as depositories of vehicular pollution are presented. Tree leaf surfaces (Lime: Tilia europaea; Sycamore: Acer pseudoplatanus) at four roadside and one woodland location in Wolverhampton, UK, have been monitored (July 2003 to November 2003). Mineral magnetic technologies have revealed spatial variations of particulate pollution concentration throughout the conurbation and data analysis indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The deposition of PM on tree leaves in European urban environments has been investigated by studying different deciduous tree species, such as: Acer campestre, Acer negundo, Acer pseudoplatanus, Aesculus hippocastanum, Carpinus betulus, Celtis occidentalis, Corylus colurna, Fraxinus pennsylvanica, Padus serotina, Pinus nigra, Platanus acerifolia, Platanus orientalis, Quercus ilex, Quercus robur, Salix alba, Tilia europaea, and Tilia tomentosa. [2][3][4][5][6][7]10,11,[25][26][27][28][29][30][31] Different analytical techniques have been used for leaf deposited PM10 characterisation, such as atomic absorption spectrometry (AAS), 5,27 gas chromatography-mass spectrometry (GC-MS), 27 inductively coupled plasma mass spectrometry (ICP/MS), saturation isothermal remanent magnetization (SIRM), 3,4,25,26,[29][30][31] and scanning electron microscopy (SEM), also implemented with x-ray spectroscopy (EDX). 2,5,31,32 In particular, magnetic analysis of leaf material has been pointed as a rapid, easy and relatively cheap strategy for identifying pollution hot spots, especially those related with traffic and industrial activities.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of PM on tree leaves in European urban environments has been investigated by studying different deciduous tree species, such as: Acer campestre, Acer negundo, Acer pseudoplatanus, Aesculus hippocastanum, Carpinus betulus, Celtis occidentalis, Corylus colurna, Fraxinus pennsylvanica, Padus serotina, Pinus nigra, Platanus acerifolia, Platanus orientalis, Quercus ilex, Quercus robur, Salix alba, Tilia europaea, and Tilia tomentosa. [2][3][4][5][6][7]10,11,[25][26][27][28][29][30][31] Different analytical techniques have been used for leaf deposited PM10 characterisation, such as atomic absorption spectrometry (AAS), 5,27 gas chromatography-mass spectrometry (GC-MS), 27 inductively coupled plasma mass spectrometry (ICP/MS), saturation isothermal remanent magnetization (SIRM), 3,4,25,26,[29][30][31] and scanning electron microscopy (SEM), also implemented with x-ray spectroscopy (EDX). 2,5,31,32 In particular, magnetic analysis of leaf material has been pointed as a rapid, easy and relatively cheap strategy for identifying pollution hot spots, especially those related with traffic and industrial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted that one of the most dangerous components of air pollution to human health is a mixture of liquid and solid particles called particulate matter (PM; Bell et al, 2011;Jędrychowski et al, 2011;Weuve et al, 2012). These pollutants can be divided into large PM (10-100 µm), coarse PM (2.5-10 µm), fine PM (0.1-2.5 µm) and ultra-fine PM (<0.1 µm; Power, 2009;Popek et al, 2013). PM is formed by natural forces and human activity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a high correlation between leaf Saturation Isothermal Remanent Magnetization (SIRM) and atmospheric PM [15][16][17]12]. Biomagnetic PM monitoring of leaves can, therefore, provide an easy and inexpensive way for monitoring the spatial and temporal distribution of atmospheric PM in urban environments [17], and thus offer an ideal tool for (spatial) PM assessment in low income countries [12].…”
Section: Introductionmentioning
confidence: 99%